MAKNA TRADISI LISAN DALIL MORO DAN IMPLIKASINYA TERHADAP PEMBELAJARAN ANTROPOLINGUISTIK - Nada, Anwar; Wahab, Justam (Jurnal GeoCivic, 2024)
This research was conducted due to the lack of public knowledge and awareness about oral traditions, especially Dalil Moro. What distinguishes this study from the previous research is the objective of the study. This study concentrates on the meaning of oral traditions and their application to anthropolinguistic learning. Furthermore, the objectives of this study are (1) to describe the meaning of the oral tradition of Dalil Moro and its implications for anthropolinguistic learning. (2) explain how the implications of oral tradition on anthropolinguistic learning are concerned. The method used in this study is qualitative descriptive, Qualitative research is a research procedure that produces descriptive data in the form of written or spoken words from people and observable behaviors (Jalaluddin, 2004: 22). The data collection techniques used in this study are observation, interviews, and reading and note-taking techniques. The data analysis technique used in this study is qualitative data analysis. Which is divided into several parts (Sugiono, 2015: 338) Reduction, Data Display (Data Presentation), Drawing conclusions and verification. Research Results and Conclusions ; 1). A small part of the people of Ternate city have maintained and preserved oral traditions in the form of Dalil Moro, 2) Dalil Moro as part of the cultural heritage of our ancestors which is used as a guideline for life that regulates the social order of social life in society so that human attitudes and behaviors do not go out of the cultural values and customs that have bee